Irrigation requirement, water use efficiency and bulb productivity of tuberose (Polianthes tuberosa) under varied wastewater-groundwater irrigation regimes - GURJAR, D S; KAUR, R; SINGH, K P (The Indian Journal of Agricultural Sciences, 2018)
A field experiment was conducted to assess the impact of wastewater irrigation on bulb productivity and water use efficiency in tuberose (Polianthes tuberosa L.) under varied wastewater-groundwater irrigation regimes at Water Technology Centre (WTC) farm of Indian Agricultural Research Institute, New Delhi during three consecutive years (2013-16). The experiment comprised varied wastewater irrigation schedules [at 0.6, 0.8, 1.0, 1.2 and 1.4 irrigation depth (ID)/cumulative pan evaporation (CPE) ratios], conjunctive use of ground and municipal wastewaters (at ID/CPE of 1.0) and only groundwater irrigations (at ID/CPE of 1.0) were laid-out in randomized block design with three replications. Results indicated that maximum irrigations (32 nos.) were applied in the plots where wastewater irrigations applied at 1.4 ID/CPE, whereas minimum irrigations (14 nos.) were applied in the treatment of wastewater irrigations at 0.6 ID/CPE. Irrigation requirement of tuberose was appreciable which increased from 700 mm to 1600mm with increasing ID/CPE. The data on bulb parameters such as number of bulblets (bulbs having diameter less than 20 mm), number of bulbs (bulbs having diameter more than 20 mm), bulb diameter, bulb length, weight of bulblets, weight of bulbs, and total bulb yield/plant were significantly not altered under application of wastewater irrigation at different ID/CPE, whereas appreciably higher values were observed in the treatment where wastewater irrigations were applied at 1.2 ID/CPE.